2018
DOI: 10.3390/w10081065
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Functional Potential of Stormwater Microorganisms Colonizing Sand Filters

Abstract: Stormwater management is increasingly relying on engineered infiltration systems (EIS) to reduce the volume and improve the quality of managed stormwater. Yet, EIS in the field will be colonized by a diverse array of environmental microorganisms that change the physiochemical properties of the EIS and provide a habitat for microorganisms with harmful or beneficial qualities. Understanding factors influencing the composition and stability of microbial communities could open up strategies for more efficient mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…All three genera were found in stormwater runoff from a previous study. 41 Effect of Bacterial Strains on Colloid Transport through Sand and Glass Bead Columns. To determine how natural bacterial strains isolated from urban stormwater alter colloid transport through porous media, we allowed strains to individually colonize sand columns for 72 h. While laboratory conditions and strains used in this experiment will not accurately recreate conditions experienced in the field, the use of standardized controlled media and flow conditions allows differences in transport to be attributed solely to properties of the bacterial strains rather than changes to differences in the fluid, filtration media, or environmental conditions, which has implications for the extent to which bacterial colonization alone can contribute to variable filter performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All three genera were found in stormwater runoff from a previous study. 41 Effect of Bacterial Strains on Colloid Transport through Sand and Glass Bead Columns. To determine how natural bacterial strains isolated from urban stormwater alter colloid transport through porous media, we allowed strains to individually colonize sand columns for 72 h. While laboratory conditions and strains used in this experiment will not accurately recreate conditions experienced in the field, the use of standardized controlled media and flow conditions allows differences in transport to be attributed solely to properties of the bacterial strains rather than changes to differences in the fluid, filtration media, or environmental conditions, which has implications for the extent to which bacterial colonization alone can contribute to variable filter performance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Bacterial strains were isolated from the effluent of sand columns inoculated with actual stormwater in an earlier study. 41 Strains were isolated from the effluent spread on NESS agar plates incubated at 22 °C for 5 days and repeated streaked on NESS agar plates to purity. Strains were characterized by comparing the V4 region of the 16S ribosomal RNA (rRNA) gene to named species in the non-redundant nucleotide database (GenBank) through BLAST.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The four stormwater bacterial strains include one strain from Sphingobacterium (SW1, GenBank accession number: MW349587 ), two strains from Chryseobacterium (SW2 and SW3, GenBank accession numbers: MW349584 and MW349583 , respectively), and one strain from Pseudomonas (SW4, GenBank accession number: MW349585 ). These strains were randomly isolated from a set of laboratory-scale sand columns inoculated with stormwater runoff collected near Johns Hopkins Homewood campus (Baltimore, MD) in a previous study ( 68 ). Our earlier study demonstrated that under the growth condition identical to that of the present study (i.e., growth media chemistry, temperature and length of growth period), all strains can attach to glass coverslips and affect repulsion and adhesion characteristics to a model colloid (carboxyl-modified-latex beads) even in areas of the slide where cells are not present.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, chemical treatments are often used for disinfection with chlorine, ozone, and UV typically used based on their ability to economically kill a variety of pathogens (Clark & Pitt, 2012; Hussain, De las Heras, Asghar, Brown, & Roberts, 2014; Mickova, 2015). Examples of biological treatments include xed growth, suspended solids growth, trickling lters, activated sludge, rotating biological contactor, facultative ponds, and aerated lagoons (Clark & Pitt, 2012;Fraser et al, 2018;Mickova, 2015;Mohanty et al, 2014;. In general, these conventional processes are reasonably effective when used individually, or in treatment process trains; however, these may not be as effective in treating more complex and recalcitrant wastewater contaminants (Chauhan, Dinesh, Alawa, & Chakma, 2021).…”
Section: Introductionmentioning
confidence: 99%